Diseño de una hostería ecológica en el sitio “El Arrastradero” parroquia Calceta, cantón Bolívar - Manabí. - Cedeño Cevallos, Toyis Edilma (2012)
The authoresses of the design Toyis Cedeño Cevallos and Yadira Párraga Basurto propose as title of the investigation the Design of an inn with characteristics ecological; by means of the application of technologies and methods of investigation that allow to obtain the information necessarily of the fields of application where this one directed to gesticulate of the ecological inn. The authoresses propose as general aim: Parish Designs an ecological inn directed to the protection of the natural resources and tourist attractions, contributing to the improvement of the quality of life of the residents in the community The Careening place, Stocking, Canton Bolivar. Since specific aims describe the following ones: To elaborate the theoretical referential frame of the investigation to near the contextualización of an ecological inn and his incident in the local community, the second one he identifies as the structure of a procedure in his phases, stages and methods that they contribute to the creation of an ecological inn located in rural spaces, finally, one proceeds to the application of the design for the creation of an ecological inn in the locality of the site The Careening place. The results of this investigation are recounted to the improvement of the quality of life of the local community to the preservation and conservation of the natural and attractive resources, as well as, the rescue of the cultural and gastronomic traditions of the locality. Finally, one has presented a technical report to the corresponding authorities and community resident authors in the community I object of study.